Fire-extinguishing performance and gas-phase pollution characteristics of different foam agents in extinguishing transformer oil pool fire. (November 2022) - Zhang, Jiaqing; Shang, Fengju; Zhou, Wencheng; Xiao, Fei; Cheng, Dengfeng
In this study, aqueous film-forming foam, fluoroprotein foam, and synthetic foam were applied to extinguish the transformer oil pool fires. The fire-extinguishing performance and burn-back resistance were investigated using a laboratory fire-extinguishing system. Moreover, the emission products were analyzed to evaluate the gas-phase pollution characteristics. Results show that aqueous film-forming foam presents the highest fire-extinguishing efficiency, while fluoroprotein foam has the best burn-back performance. Flue gas and gas chromatography–mass spectrometer analyses demonstrate that the use of fluoroprotein foam results in much higher CO emissions than other foams, and the pollutants are mainly from various hydrocarbons produced by incomplete combustion of transformer oil. Synthetic foam and aqueous film-forming foam lead to higher SO2 and NO emissions, and pollutants are mainly dominated by alcohols and ethers. Noteworthily, when using aqueous film-forming foam to extinguish oil pool fire, a persistent organic pollutant, perfluorooctanoic acid, is detected in the gas phase.